ÍNDICE DE APERTURA LEGAL PARA EL REGISTRO DE PARTIDOS POLÍTICOS LOCALES EN MÉXICO. - González Padilla, Roy (Andamios)
This article discusses the creation and registration of local political parties in Mexico. The author comments on the legal aspects and regulations involved in the development of political parties and describes the party system that is established in the country. He also considers the recent history of Mexican politics. The impact of these local political parties on the national political environment is examined and the creation of political parties as a response to historical events is also analyzed.